Do different multi‐segment foot models detect the same changes in kinematics when wearing foot orthoses? - Tomas Klein; Graham J. Chapman; Ondrej Lastovicka; Miroslav Janura; Jim Richards (Journal of Foot and Ankle Research, 2022)
Abstract Background Different multi‐segment foot models have been used to explore the effect of foot orthoses. Previous studies have compared the kinematic output of different multi‐segment foot models, however, no study has explored if different multi‐segment foot models detect similar kinematic changes when wearing a foot orthoses. The aim of this study was to compare the ability of two different multi‐segment foot models to detect kinematic changes at the hindfoot and forefoot during the single and double support phases of gait when wearing a foot orthosis. Methods Foot kinematics were collected during walking from a sample of 32 individuals with and without a foot orthosis with a medial heel bar using an eight‐camera motion capture system. The Oxford Foot Model (OFM) and a multi‐segment foot model using the Calibrated Anatomical System Technique (CAST) were applied simultaneously. Vector field statistical analysis was used to explore the kinematic effects of a medial heel bar using the two models, and the ability of the models to detect any changes in kinematics was compared. Results For the hindfoot, both models showed very good agreement of the effect of the foot orthosis across all three anatomical planes during the single and double support phases. However, for the forefoot, the level of agreement between the models varied with both models showing good agreement of the effect in the coronal plane but poorer agreement in the transverse and sagittal planes. Conclusions This study showed that while consistency exists across both models for the hindfoot and forefoot in the coronal plane, the forefoot in the transverse and sagittal planes showed inconsistent responses to the foot orthoses. This should be considered when interpreting the efficacy of different interventions which aim to change foot biomechanics.